Macromer reinforced pressure sensitive skin adhesive sheet material - TAYLOR; CHARLES W; KRAMPE; STEPHEN E; MOORE; CHERYL L (1988)
A skin adhesive coated sheet material is provided which is coated with a polymer that exhibits an enhanced level of initial adhesion when applied to skin but resists objectionable adhesion build up over time. The skin adhesives are comprised of a macromer reinforced acrylate copolymer which has a creep compliance value at least about 1.2x10-5 cm2/dyne. A stable chemical complex of iodine, iodide and a pressure-sensitive adhesive is also provided wherein the adhesive has a creep compliance value of at least about 1.0x10-5 cm2/dyne measured when the adhesive composition is substantially free of iodine.